Classroom Interaction in Teaching English for Mechanical Engineering Students - Dharmawati Dharmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This descriptive qualitative research deals with classroom interaction in teaching English for mechanical engineering students. This research aims at finding out and describing the classroom interaction of mechanical engineering class at Universitas Harapan Medan. The purpose of this study is to figure out the patterns of classroom interaction in English teaching learning process for mechanical engineering class. The methods used in collecting data were observation and interview. The data were in the form of words, clauses, and sentences that carried out by video, and in-depth interview transcripts. The participants were an English lecturer and twenty two mechanical engineering students. The technique of data analysis used data collection, data diplay and drawing conclusion. The result of this research was dominated by the interaction between the teacher and students. The percentage of using English  between lecturer and students’ interaction is 40 %. It happened because the students had difficult to respon the lecturer’s question in English.